OPTIMIZING AMIL'S PERFORMANCE IN MANAGING ZISWAF FUNDS AT DOMPET DHUAFA - Endar Muda; Maghfirah Maghfirah (SEAN Institute, 2023)
Zakat has a horizontal dimension between God and humans and vertically between humans and humans is consistent with issuing Zakat, Infaq and Sadaqah as part of the obligations of Muslims. Talented human resources are needed to manage the funds allocated so that these funds are channelled to parties entitled to these funds. In this case, this study is based on a survey of the phenomena occurring in Zakat collection institutions' human resources. Seeing the responsibilities and authorities carried out by Zakat institutions is also quite complex; this can be seen from the impact of human resources on the performance of Zakat institutions. The role of human resources is to become a professional asset of an Amil Zakat institution with certain standards. This article aims to understand the strategic role of human resource management in managing Zakat, infaq, and sadaqah funds through literature, legal regulations, and empirical evidence